2006
DOI: 10.1146/annurev.fluid.38.050304.092208
|View full text |Cite
|
Sign up to set email alerts
|

SCALING: Wind Tunnel to Flight

Abstract: Wind tunnels have wide-ranging functionality, including many applications beyond aeronautics, and historically have been the major source of information for technological aerodynamics/aeronautical applications. There are a myriad of scaling issues/differences from flight to wind tunnel, and their study and impacts are uneven and a function of the particular type of extant flow phenomena. Typically, the most serious discrepancies are associated with flow separation. The tremendous ongoing increases in numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Sub-designscale testing is standard practice in the field of hypersonics due to size constraints imposed by the available wind tunnel facilities. Typically, to achieve similitude of the flow field between a sub-scale wind tunnel experiment and full-scale flight article, some form of scaling of the flow condition is required (Bushnell, 2006;McGilvray et al, 2010). The predominant scaling method used for supersonic combustion experiments is the binary scaling method (Hornung, 1988;Stalker and Pulsonetti, 2004) for which the flow velocity, temperature and gas composition of the test condition are matched to flight while the density is adjusted such that the product of density and length remains constant.…”
Section: Influence Of Flight Dynamic Pressurementioning
confidence: 99%
“…Sub-designscale testing is standard practice in the field of hypersonics due to size constraints imposed by the available wind tunnel facilities. Typically, to achieve similitude of the flow field between a sub-scale wind tunnel experiment and full-scale flight article, some form of scaling of the flow condition is required (Bushnell, 2006;McGilvray et al, 2010). The predominant scaling method used for supersonic combustion experiments is the binary scaling method (Hornung, 1988;Stalker and Pulsonetti, 2004) for which the flow velocity, temperature and gas composition of the test condition are matched to flight while the density is adjusted such that the product of density and length remains constant.…”
Section: Influence Of Flight Dynamic Pressurementioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] In the case of the simulation of transonic flow, the situation becomes even more complex when defining the aerodynamic flow parameters. The effects of solid and flow blockage are even more evident, the side-wall boundary layer becomes thicker and areas of separated flow and shock waves are created, which cannot even be eliminated by the full presence of ventilated transonic walls.…”
Section: -7)mentioning
confidence: 99%
“…Many of these results have been achieved by outstanding and widely known international aerodynamic institutions. For example, an analysis has been made of some old wind tunnel low-speed tests conducted by the NACA Institute (symbols 2-4), contemporary results of NASA (1, 5 and 6), results achieved in very good industrial facilities (10)(11)(12), detailed studies of the NPL and RAE (13)(14)(15), the results achieved by AGARD working group 04 DATA BASE (17), the results of ONERA (16)(17)(18)(19), of the VTI and the Faculty of Mechanical Engineering (21).…”
Section: Analysis Of Problemmentioning
confidence: 99%
“…Further, laboratory research enables reproducible investigation of key small-scale processes that can be of central significance. Examples of successes that span across laboratory and heliophysical plasma physics research include the development of accurate atomic physics databases [4]; shuttle reentry and aeronautical flight [18]; and, understanding whistler wave dynamics [19][20][21][22]. The NRL gathering participants, all of whom are co-authors of this report, identified the following areas that are ready for coupled research in space-based Sun-Earth system research and laboratory-based confined plasma research.…”
Section: Identified Areas For Possible Coupled Researchmentioning
confidence: 99%